A simulation analysis of mobility models for network mobility environments - Islam, Shayla; Hassan Abdalla Hashim, Aisha; Habaebi, Mohamed Hadi; Abd Latif, Suhaimi; Hasan, Mohammad Kamrul (Asian Research Publishing Network (ARPN), 2015)
In real world scenarios, there is an increasing concern in placement as well as assessment of mobility management protocols for Network Mobility (NEMO). Mobility models have a substantial impact on the performance evaluation of any new mobility management protocol in NEMO. A considerable assessment of any protocol and comparison with other equivalent protocol cannot be completed without making use of an accurate mobility model. The choice of the mobility model can majorly affect the performance assessment of mobility protocols. As a result, it is really essential to pick a detailed mobility model which correctly symbolizes the movement pattern of Mobile Routers (MRs). This paper details the most prevalent mobility models utilized such as Random Way Point (RWP) and Constant Velocity (CV) mobility model to characterize the MR mobility rate in NEMO. After that, Network Simulator version 3 (NS-3) simulation results will be presented using movement pattern of MR as well as road maps to show the significance of selecting an appropriate mobility model on PMIPv6 domain in NEMO (PNEMO) environment.